What is a good school, and can parents tell? Evidence on the multidimensionality of school output - Diether W. Beuermann; Clement Jackson; Laia Navarro-Sola; Francisco Pardo (Inter-American Development Bank (IDB), 2019)
Is a school's impact on high-stakes test scores a good measure of its overall impact on students? Do parents value school impacts on high-stakes tests, longer-run outcomes, or both? To answer the first question, we apply quasi-Experimental methods to data from Trinidad and Tobago and estimate the causal impacts of individual schools on several outcomes. Schools' impact on high stakes tests are weakly related to impacts on low-stakes tests, dropout, crime, teen motherhood, and formal labor market participation. To answer the second question, we link estimated school impacts to parent's ranked lists of schools and employ discrete choice models to estimate parental preferences. Parents value schools that causally improve high-stakes test scores conditional on average outcomes, proximity, and peer quality. Consistent with parents valuing the multi-dimensional output of schools, parents of high-achieving girls prefer schools, parents of high-achieving girls prefer schools that increase formal labor market participation, and parents of high-achieving boys prefer schools that reduce arrests.
Keywords: I2; J01; J38; 330; Trinidad and Tobago; school quality; school preferences